2007
DOI: 10.1073/pnas.0707766104
|View full text |Cite
|
Sign up to set email alerts
|

Competitive release and facilitation of drug-resistant parasites after therapeutic chemotherapy in a rodent malaria model

Abstract: Malaria infections frequently consist of mixtures of drug-resistant and drug-sensitive parasites. If crowding occurs, where clonal population densities are suppressed by the presence of coinfecting clones, removal of susceptible clones by drug treatment could allow resistant clones to expand into the newly vacated niche space within a host. Theoretical models show that, if such competitive release occurs, it can be a potent contributor to the strength of selection, greatly accelerating the rate at which resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
210
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(221 citation statements)
references
References 61 publications
11
210
0
Order By: Relevance
“…45 Similarly, with malaria it has been proposed that when sensitive and resistant parasites co-infect the same host individuals, drug use would further increase the relative fitness of drugresistant clones by removing drug-sensitive competitors. 46 It may seem that there is a discrepancy between the decrease in fungal burden and the lack of response in survival of G. mellonella infected with A. lentulus in the single and the mixed infection. It has been described that A. lentulus VRC MICs range from 4 to 6 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…45 Similarly, with malaria it has been proposed that when sensitive and resistant parasites co-infect the same host individuals, drug use would further increase the relative fitness of drugresistant clones by removing drug-sensitive competitors. 46 It may seem that there is a discrepancy between the decrease in fungal burden and the lack of response in survival of G. mellonella infected with A. lentulus in the single and the mixed infection. It has been described that A. lentulus VRC MICs range from 4 to 6 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…those >5 years old in a high transmission area, may also help to reduce the spread of resistance to ACTs. Wargo et al 15 have shown that the development of resistant strains might in fact be slower when parasite clearance is not achieved: where subcurative chemotherapy was administered, the resistant clone was only partly released from competitive suppression and experienced a restriction in the size of its expansion after treatment.…”
Section: Meaning Of the Study: Possible Explanations And Implicationsmentioning
confidence: 99%
“…This can lead to increased gametocyte production in multiple-clone infections, which may have a major public health impact even in those areas where early diagnosis and treatment of malaria can be achieved (Sattabongkot et al 2004). In addition, when clone mixtures are comprised of drug-resistant and drug-sensitive P. chabaudi strains, the removal of susceptible clones by drug therapy promoted the expansion of resistant parasites to a level far beyond that achieved when a competitor had never been present (Wargo et al 2007). Therefore, these experimental results imply that within-host competition may accelerate the spread of drug resistance in malaria parasites.…”
Section: Prevalence and Consequences Of Multiple-clone P Vivax Infecmentioning
confidence: 99%